2016
DOI: 10.1103/physreve.94.052702
|View full text |Cite
|
Sign up to set email alerts
|

Inverse stochastic resonance in electroconvection by multiplicative colored noise

Abstract: A kind of inverse stochastic resonance (ISR) observed in ac-driven electroconvection (EC) in a nematic liquid crystal is presented. In successive pattern evolutions by increasing noise intensity V_{N}, a typical EC (with a normalized amplitude A_{0}=1 at V_{N}=0) disappears (A_{0}→0), and then the rest state (A_{0}=0) reenters into the EC (A_{0}=1); eventually, it develops into complicated EC(A_{0}>1). The reversed bell-shaped behavior of A_{0}(V_{N}) is evidence of ISR. The present ISR may be explained by tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 42 publications
5
23
0
Order By: Relevance
“…Furthermore, ISR might also play a critical role in computational mechanisms that require reduced firing activity without chemical inhibitory neuromodulation or, alternatively, when other computational mechanisms require on-off bursts of activity. On the other hand, apart from neural systems, a recent experimental study reported the existence of ISR in nematic liquid crystals (NLC) [23]. This work shows that a proper arrangement of colored noise intensity and its correlation time constant induces ISR in an ac-driven electroconvection in NLC.…”
Section: Introductionmentioning
confidence: 81%
“…Furthermore, ISR might also play a critical role in computational mechanisms that require reduced firing activity without chemical inhibitory neuromodulation or, alternatively, when other computational mechanisms require on-off bursts of activity. On the other hand, apart from neural systems, a recent experimental study reported the existence of ISR in nematic liquid crystals (NLC) [23]. This work shows that a proper arrangement of colored noise intensity and its correlation time constant induces ISR in an ac-driven electroconvection in NLC.…”
Section: Introductionmentioning
confidence: 81%
“…In contrast, an opposing phenomenon known as the inverse stochastic resonance (ISR) was initially discovered in a neural system [14][15][16], showing a minimal output performance peak at a moderate optimal noise intensity. Later, ISR was also reported in other systems such as ecological systems and during electroconvection (EC) [17,18].…”
Section: Introductionmentioning
confidence: 90%
“…( 1) is additive, i.e., independent of the variable x [21,22]. Similarly, multiplicative noise (t) (i.e., x(t)) can provide SR [22][23][24] and ISR [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noise is ubiquitous in the neural system, caused by thermal effects, activity of ion channels and etc. [13,14]. The appropriate noise plays an important role in information transmission and detection, which can induce stochastic resonance (SR), and optimizing the detection and propagation of weak signals [15][16][17][18].…”
mentioning
confidence: 99%